Implementation of Jurimetry in Determining Compensation in the Realm of State Administrative Court - Eka NAM Sihombing; Cynthia Hadita; Novita Sartika Elisabeth (Asosiasi Pengajar Hukum Tata Negara dan Hukum Administrasi Negara, 2026)
The development of legal technology encourages the presence of a quantitative approach in judicial practice, one of which is through jurimetry. In the context of the State Administrative Court (PTUN), the determination of compensation often faces challenges due to the lack of standard standards and the disparity of decisions. This study aims to analyze the implementation of jurimetry in determining the amount of compensation in the PTUN as an effort to realize legal certainty and measurable justice. The method used is socio-legal research. The results of the study show that the application of jurimetry can be an effective instrument in minimizing the subjectivity of judges through the use of a database of previous decisions and quantitative variables such as the value of material losses, non-material impacts, and the level of official errors. However, the implementation of jurimetry is still limited due to the limitations of data infrastructure and resistance to quantitative approaches in judicial practice. This study concludes that strengthening regulations and digitizing PTUN decision data is needed to support jurimetry as a more transparent and consistent compensation determination mechanism.